Mitigating a traffic impact on animals - Nowacka, Dagmara (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Poland, which biological diversity stands out in comparison with the rest of Europe, became one of the biggest road construction site during the last few years. A development of a road network almost always involves disturbance of biogically sensitive and protected areas. As those areas cover about one third of the whole country it is virtually impossible to avoid conflicts concerning biological protection. For those reasons, steps to be taken to limit to a minimum the incidence of the construction works on the biological environment constitute an integral part of each investment. The costs of protecting unspoiled environment represent up to 30% of the total costs of investments. The effectiveness of planned actions must consequently justify spending the considerable funds involved. Monitoring of the results of solutions used allows both verification of their usefulness and identification possible errors so that they may be avoided in the future. Number of actions which have been undertaken in Poland to minimalize the incidence of roads on unspoiled environment, in particular as regards the number of fauna passes, to preserve the ecological continuity, place Poland among most advanced European countries.